LIPID PROFILE, FUNCTIONAL CAPACITY AND ANKLE-BRACHIAL INDEX IN ACTIVE OLDER ADULTS - Marques,Terezinha Sasaki (2019)
ABSTRACT Introduction: Regular physical activity prevents cardiovascular diseases (CVD) and atherosclerosis, in addition to improving lipid levels and functional capacity in older adults. Objective: To evaluate and compare the lipid levels, functional performance and ankle brachial index (ABI) of sedentary and active older adults. Methods: This was a comparative cross-sectional study with 84 elderly (≥60 years) male and female subjects, divided into two groups: sedentary group (SG, n = 50) and active group (AG, n = 34) according to the International Physical Activity Questionnaire (IPAQ). Anthropometric and hemodynamic assessments, ankle brachial index (ABI) calculations, and functionality tests (Short Physical Performance Battery - SPPB and 6-minute walking test - 6MWT) were performed. The Shapiro-Wilk normality test was also used, and we conducted the Student's-t and Mann-Whitney tests for the intergroup comparison. For the categorical data, we used Fisher's exact test (p <0.05). Results: Higher values of high-density lipoprotein cholesterol (HDL-c) (p = 0.001) and lower triglycerides (TG) (p = 0.007) were found in AG compared to SG. In the ABI evaluation, AG presented better right (p = 0.012), left (p = 0.015) and end (p = 0.004) ABI rates when compared to SG. AG had better results in functional performance in the SPPB evaluation (p = 0.0007) and in the 6MWT with a greater distance covered (p = 0.0027). In the anthropometric measurements, AG had lower body mass index (BMI) (0.041) and a smaller abdominal circumference (WC) (0.029). In terms of the incidence of referred diseases, intergroup results were only different for hypertension (0.029), while AG had a lower incidence of hypertension. Conclusion: Active older adults had better lipid levels, higher ABI levels, better functional performance, lower body mass, a smaller abdominal circumference, and lower incidence of hypertension, in comparison to sedentary subjects. Level of evidence I; High quality prospective study.